Relation of chest HRCT scan findings with hematological, biochemical, and immunological parameters of hospitalized Covid-19 patients in a tertiary hospital in Chattogram city - Tabassum, Nafisa (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.